Prevalence of tuberculosis in the State of Pará between 2015-2019 (Research, Society and Development, 2021)
The goals was to relate the prevalence of tuberculosis in some cities in the state of Pará between the years 2015 to 2019 and accumulated details about the disease. The research is descriptive, observational and retrospective through a view of data obtained from the Ministry of Health website and the tuberculosis database at DATASUS to analyze epidemiologically and numerically the cases of tuberculosis registered in the municipalities, registered between the years 2015 to 2019. With the data found, it was perceived that there was stability during the last 5 years, however, there was a substantial increase from 2018 to 2019 in the city of Marituba. Regarding the age group, in the five-year period of people with tuberculosis, it was between 20-39 years old and 40-59 years old, with the highest number of cases in the municipality of Belém. of cases in the municipality of Belém. It is concluded that through this research, it will be feasible to train health professionals for possible cases of outbreaks or future epidemics, estimate more precise amounts of medicines, demand for resources on the maintenance of infrastructure, among other intervention measures.